Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.chemmater.7b05311
|View full text |Cite
|
Sign up to set email alerts
|

MnSb2S4 Monolayer as an Anode Material for Metal-Ion Batteries

Abstract: We present density functional calculations showing that monolayer MnSb2S4 is promising as an anode material for Li-, Na-, and Mg-ion batteries, and that the adsorption of Zn or Al atoms on the surface of MnSb2S4 monolayer is not energetically favorable. The calculations show electron transfer from Li, Na, or Mg to the empty orbitals of nearby Sb and S atoms. The calculations indicate that an adsorption mechanism is followed by a conversion mechanism during charging, and the storage capacities can reach as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Luo et al [26] reported that layered Na 2 Ti 6 O 13 nanowires display a stable capacity of 51.2 mA h/g at 100 mA/g after 300 cycles. Many theoretical calculations have verified that layered materials, such as arsenene [27], MnSb 2 S 4 [28], MXene [29], phosphorene [8], WS 2 [30], and C 3 N 4 [31], can be promising anode materials for MIBs. Furthermore, 2D layered transition metal phosphorous trichalcogenides (MPX 3 , where M = Mn, Fe, Ni, etc., and X = S, Se) have been widely explored because of their interesting physicochemical features, including electronic, magnetic, and superconductive properties [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [26] reported that layered Na 2 Ti 6 O 13 nanowires display a stable capacity of 51.2 mA h/g at 100 mA/g after 300 cycles. Many theoretical calculations have verified that layered materials, such as arsenene [27], MnSb 2 S 4 [28], MXene [29], phosphorene [8], WS 2 [30], and C 3 N 4 [31], can be promising anode materials for MIBs. Furthermore, 2D layered transition metal phosphorous trichalcogenides (MPX 3 , where M = Mn, Fe, Ni, etc., and X = S, Se) have been widely explored because of their interesting physicochemical features, including electronic, magnetic, and superconductive properties [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Ad istinction is that in the former the oxidation of Oi st riggered earliera nd Fe 4 + (t 3 2g e Ã1 g )i nL NFMO activatesOions with an ear-linear O-Fe-Oc onfiguration, which may provide higher capacity than LNCMO.F es ubstitution can restraino xygen release and potentialf ading to ac ertain extent compared with LNCMO;0 .44 ep er Li (Li 0.17 For most of the lithium-rich layered oxides, high capacities cannotb es ustained during prolongedc ycling because of excessive oxidationo fOi ons. Similar to the work of Huang et al, [50] for all the LS and HS states, coupling between the Fe 3 + ions may be ferromagnetic (FM) or antiferromagnetic (AFM). Figure 1a).…”
Section: Discussionmentioning
confidence: 60%
“…Figure 1a). We applied the simplified approach to the GGA + U method introduced by Dudarev et al, [47] in which the parameters U and J do not enter separately,a nd only the difference (UÀJ)i sm eaningful;h ence, we will simply call the parameter U, similar to the work of Huang et al [48,49] The redox process of the Co-containing Li-rich Li (Li 0.17 [50] for all the LS and HS states, coupling between the Fe 3 + ions may be ferromagnetic (FM) or antiferromagnetic (AFM). The calculated results show that the energy of Li 28Àx Ni 4 Fe 4 Mn 12 O 48 in the FM state is higher than that in the AFM state, except for x = 0, 14, and 24.…”
Section: Discussionmentioning
confidence: 99%
“…7, we list some typical 2-D anode materials for the maximum capacity of NIBs. They include Ti 3 C 2 (352 mA h g À1 ), 26 Mn 2 C (444 mA h g À1 ), 72 2-D GaN (625 mA h g À1 ), 73 blue phosphorene (865 mA h g À1 ), 71 black phosphorene (865 mA h g À1 ), 72 MnSb 2 S 4 (879 mA h g À1 ), 74 GeP 3 (1295 mA h g À1 ), 75 and b 12 /c 3 borophene (1240/1984 mA h g À1 ). 23,24 It is very exciting to note that the maximum Na-ion capacity of the current CP 3 monolayer is up to 2298.9 mA h g À1 , which is much higher than all the examples listed in Fig.…”
Section: Storage Capacity and Open Circuit Voltagementioning
confidence: 99%